Chondrocyte affinity peptide modified PAMAM conjugate as a nanoplatform for targeting and retention in cartilage. (4th May 2018) - Hu, Qing; Chen, Qing; Yan, Xiuyun; Ding, Bomei; Chen, Dawei; Cheng, Lifang
Aim: To develop a nanocarrier for targeted delivery of agents to the cartilage.Materials & methods: Chondrocyte affinity peptide modified PEGylated polyamidoamine conjugates (CAP-PEG-PAMAM) were prepared and rhodamine B isothiocyanate (RB) fluorophore was linked on them for comparative biological tracing and profiling.Results: CAP4-PP-RB exhibited much more efficient cellular uptake in vitro than that of PEG-PAMAM-RB. Both the conjugates were likely internalized by chondrocytes via clathrin and caveolin co-mediated endocytosis, and delivered to lysosomes. In vivo imaging demonstrated the fluorescein-labeled nanocarrier was capable to persist in the joint cavity of rats for a prolonged time. Furthermore, the CAP4-PEG-PAMAM showed a good biocompatibility and enhanced penetration effects in vivo .Conclusion: CAP-PEG-PAMAM could be an effective nanocarrier for intra-articular delivery of agents to cartilage.